The Handbook of international crisis communication research - 4 0 16; (Matthew Wayne), 1979-;1957-;1984- Schwarz, Andreas,;Seeger, Matthew W.;Auer, Claudia; 5 (Chichester, UK ;;Malden, MA : Wiley Blackwell, 2016)
The Handbook of International Crisis Communication Research articulates a broader understanding of crisis communication, discussing the theoretical, methodological, and practical implications of domestic and transnational crises, featuring the work of global scholars from a range of sub-disciplines and related fields. -Provides the first integrative international perspective on crisis communication -Articulates a broader understanding of crisis communication, which includes work from scholars in journalism, public relations, audience research, psychology, political science, sociology, economics, anthropology, and international communication -Explores the topic from cross-national and cross-cultural crisis communication approaches -Includes research and scholars from countries around the world and representing all regions -Discusses a broad range of crisis types, such as war, terrorism, natural disasters, pandemia, and organizational crises.
Disciplinary foundations for international crisis communication research -- Actors and institutional communicators in international crises -- The role of the media in the construction of international crises -- Domestic and international audiences in the cocntext of crisis communication -- The state of crisis communication research around the globe -- Challenges and topics of future research on crisis communication.
Includes bibliographical references and index.
Description based on print version record.
Keywords: 2 -- 0; 6; Crisis management;Risk communication;Communication, International -- 20 -- Handbooks, manuals, etc.;Handbooks, manuals, etc.;Handbooks, manuals, etc; 20; Electronic books.;Handbooks and manuals.;Electronic books